The Implementation of Global Diversity Dimension on Final Stage of Foundation Phase in Islam-Based Institution - Oktaviani, Annastasya; Ali Formen (Universitas Negeri Semarang, 2025)
The aim of this study is to understand the interpretation and the process of implementing the global diversity dimension at the Final of the Foundation Phase at TK Bina Citra Cendekia. This research employs a descriptive qualitative approach. The data is collected through interviews, observations, and documentation. The data analysis technique in this study uses Miles and Huberman’s technique, which includes data collection, data reduction, data presentation, and conclusions. This research found that TK Bina Citra Cendekia interprets the global diversity dimension into three main ideas, namely: (1) understanding the concept of self and environment, (2) appreciation of diversity, and (3) global diversity as part of moral education. Based on the key elements of the global diversity dimension, the implementation at TK Bina Citra Cendekia is described in six categories, namely: (1) strengthening the concept of self and environment, (2) opening the student’s minds through the reinforcement of the concept of diversity, (3) honing tolerance through the introduction of cultural diversity, (4) building intercultural communication skills, (5) fostering awareness to collaborate in social life, and (6) integrating the values of diversity with Islamic values.